Leader's relational power: Concept, measurement and validation. Issue 5 (October 2016) - Zhao, Xinyu; Shang, Yufan; Lin, Jun; Tan, Jia; Li, Haiyun; Liu, Ting
Abstract: Previous research on a leader's relational power has mainly focused on the conceptualization of this emerging concept, and issues on taxonomy and measurement are not fully addressed or understood. Hence, the independence of a leader's relational power is not adequately elaborated. The present study reinterprets relational power from a taxonomic perspective and develops a reliable measurement scale. Results distinguish relational power from position and personal power and further demonstrate that relational power is an independent power source that comprises two subtypes, namely, direct and indirect relational power. We define the concept of a leader's relational power and then summarize all items related to relational power through a literature review, interviews, and semi-structured questionnaires. With the help of experts in this area, we generate the preliminary relational power scale, which includes the following steps: cataloguing, summarizing, pretesting, and revising. We then construct the formal relational power scale using item analysis and exploratory factor analysis. We verify the two-dimensional structure of relational power using confirmatory factor analysis. Finally, we apply theoretical and empirical methods to test whether relational power is independent from position and personal power.